(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
Which ontology underlies the main models of cognition? What did the cognitive paradigm bring about? Which philosophical commitment we assume when, conscious or not, we tinge our conception of what is real, especially of intelligent biological systems, with the explanation we give of the functioning of an information system? The hypothesis we maintain is that, with regards to cognition and the naturalistic and emergentist conceptual frame, we must (and can) recognize the limits of what is explainable and what is not.